Metode Penerjemahan Majas pada Lagu Rohani Karya Lauren Kaori - Nari, Denny Charles; Artana, I Nyoman Rauh (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 1 (2021)DO - 10.24843/JS.2021.v03.i01.p03, 2021)
This research  entitled "The Translation Method of  Figurative Language in  Spiritual Songs by Lauren Kaori" Aims of this research is to find out the types of  figure of speech contained in Lauren Kaori's spiritual songs as well as figurative langugage of  translation methods used in translating figure of speech on spiritual songs by Lauren Kaori. This research was analyzed using a qualitative descriptive method. The theory used in this research is figurative language theory according to Seto (2002), and figurative language theory according to Knickerbockers and Reninger (1963), Newmark's theory of translation methods (1998). Sources of data for this research were taken from Lauren Kaori's YouTube channel, including Cory Asbury's “Reckless Love”, Elevation Worship's “O Come To The Altar”, Hillsong Worship's “What A Beautiful Name”, Bethel Worship's “King Of My Heart” , “10000 Reasons (Bless the Lord)” by Matt Redman, “Oceans (Where Feet May Fail)” by Hillsong United. The results of this study indicate 1). hyperbolic figures of speech, metaphor, personification, tautology, synesthesia, and seven data were also found to experience a shift in translation results in translating language from BSu into BSa. 2). The translation method used is the free method, the semantic method, the communicative method, word to word method, and the literal method.